PENGENDALIAN PERSEDIAAN BAHAN BAKU PEMBUATAN SANDAL DENGAN MENGGUNAKAN METODE LOT FOR LOT (LFL) DAN PERIOD ORDER QUANTITY (POQ) DI CV SINAR MAS - Farhana, Fira; Satoto, Handy Febri (Universitas Majalengka, 2024)
CV Sinar Mas is a company in the Footwear manufacturing sector. Based on data, demand for footwears fluctuates, causing CV Sinar Mas difficulty in producing the number of raw materials for footwears ordered. The company also has not used an optimal raw material inventory control system. Therefore, the company experienced an excess of raw materials which occurred in November-December 2023, resulting in a buildup of raw materials which caused high production costs and decreased quality because it was too piled up in the warehouse. So, there must be planning and control of the availability of raw materials in order to obtain minimal costs and maintain the quality of raw materials. This research uses the Lot Sizing method, namely LFL (Lot For Lot) and POQ (Period Order Quantity). The goal is to determine the order quantity with minimal costs.